Pengaruh Corporate Social Responsibility (CSR), dan Profitabilitas terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Kontrol - Revha Septia Ranika; Hesi Eka Puteri (Lembaga Yasin AlSys, 2026)
Firm value is an important indicator that reflects investors’ perceptions of a company’s performance and prospects. Although the effect of Corporate Social Responsibility (CSR) and profitability on firm value has been widely examined, studies that specifically analyze these two variables with firm size as a control variable in food and beverage companies listed on the Indonesia Sharia Stock Index (ISSI) for the 2021–2024 period remain limited. This study aims to analyze the effect of CSR and profitability on firm value with firm size as a control variable. This study used a quantitative approach with a causal associative design. The sample consisted of 13 food and beverage companies listed on the ISSI and selected using purposive sampling, resulting in 52 observations. Data were collected through documentation of companies’ annual reports and analyzed using panel data regression with the assistance of EViews 13. The results show that, partially, CSR has no significant effect on firm value, whereas profitability has a positive and significant effect on firm value. Simultaneously, CSR and profitability have a significant effect on firm value with firm size as a control variable. These findings contribute to the development of Signaling Theory by showing that profitability information serves as a stronger signal for investors than CSR disclosure. The conclusion of this study emphasizes the importance of profitability in increasing firm value. The implications of this study include theoretical contributions to the development of Islamic financial management literature as well as practical implications for company management in formulating strategies to improve financial performance and implement CSR more effectively. Future research is recommended to expand the sample coverage and observation period, as well as to add other variables that may potentially influence firm value.